2016
DOI: 10.3389/fncel.2016.00108
|View full text |Cite|
|
Sign up to set email alerts
|

Local Optogenetic Induction of Fast (20–40 Hz) Pyramidal-Interneuron Network Oscillations in the In Vitro and In Vivo CA1 Hippocampus: Modulation by CRF and Enforcement of Perirhinal Theta Activity

Abstract: The neurophysiological processes that can cause theta-to-gamma frequency range (4–80 Hz) network oscillations in the rhinal cortical-hippocampal system and the potential connectivity-based interactions of such forebrain rhythms are a topic of intensive investigation. Here, using selective Channelrhodopsin-2 (ChR2) expression in mouse forebrain glutamatergic cells, we were able to locally, temporally precisely, and reliably induce fast (20–40 Hz) field potential oscillations in hippocampal area CA1 in vitro (at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Although the functional significance of abnormal high-frequency EEG oscillations in these neuropsychiatric disorders is unknown, gamma oscillations have attracted a lot of attention in recent years because of the role they play in feature binding [ 43 ], object representation [ 44 ], and selective attention [ 45 ]. Gamma oscillations are generated in the cortex and hippocampus [ 46 , 47 ]. Since basal ganglia is severely affected in HD, insufficient inhibition of cortical activity by cortical projecting neurons of basal ganglia could account, at least in part, for the abnormal low-gamma EEG oscillations seen in HD [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the functional significance of abnormal high-frequency EEG oscillations in these neuropsychiatric disorders is unknown, gamma oscillations have attracted a lot of attention in recent years because of the role they play in feature binding [ 43 ], object representation [ 44 ], and selective attention [ 45 ]. Gamma oscillations are generated in the cortex and hippocampus [ 46 , 47 ]. Since basal ganglia is severely affected in HD, insufficient inhibition of cortical activity by cortical projecting neurons of basal ganglia could account, at least in part, for the abnormal low-gamma EEG oscillations seen in HD [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A). This is consistent with previous studies of ChR2‐induced CA1 gamma oscillations (Dine et al ., ), where it was observed that blocking muscarinic acetylcholine receptors with atropine eliminated these residual gamma oscillations. These results indicate that a fast excitatory–inhibitory feedback loop underlies the generation of gamma oscillations during theta‐rhythmic activation of principal cells in all three regions, consistent with a PING mechanism of generation (Fisahn et al ., ; Whittington et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In the cortex and other subcortical areas, PNNs preferentially surround GABAergic interneurons containing the calcium-binding protein parvalbumin. These specific cells have been recently identified as fast-spiking cells relevant for gamma-oscillations (Dine et al 2016 ).…”
Section: Memory Of Painmentioning
confidence: 99%